The Smartphone as a Pacifying Technology - Melumad, Shiri; Pham, Michel Tuan (Journal of Consumer Research, 2020)
AbstractIn light of consumers’ growing dependence on their smartphones, this article investigates the nature of the relationship that consumers form with their smartphone and its underlying mechanisms. We propose that in addition to obvious functional benefits, consumers in fact derive emotional benefits from their smartphone—in particular, feelings of psychological comfort and, if needed, actual stress relief. In other words, in a sense, smartphones are not unlike adult pacifiers. This psychological comfort arises from a unique combination of properties that turn smartphones into a reassuring presence for their owners: the portability of the device, its personal nature, the subjective sense of privacy experienced while on the device, and the haptic gratification it affords. Results from one large-scale field study and three laboratory experiments support the proposed underlying mechanisms and document downstream consequences of the psychological comfort that smartphones provide. The findings show, for example, that (a) in moments of stress, consumers exhibit a greater tendency to seek out their smartphone (study 2); and (b) engaging with one’s smartphone provides greater stress relief than engaging in the same activity with a comparable device such as one’s laptop (study 3) or a similar smartphone belonging to someone else (study 4).